Polyacrylonitrile nascent fiber, polyacrylonitrile-based carbon fiber and preparation method thereof

By setting up a fiber steering device and optimizing the curling roller set device in the solidification bath, the problem of broken fibers of primary fibers of polyacrylonitrile-based carbon fibers is solved, the diameter uniformity and mechanical properties of the fibers are improved, and efficient preparation of polyacrylonitrile-based carbon fibers is achieved. .

CN119308032APending Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310848241.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, primary fibers of polyacrylonitrile-based carbon fibers are prone to breaking wires in solidification baths, resulting in structural unevenness and mechanical properties degradation. In addition, existing improved methods such as fairing and guide roller designs have solvent accumulation and double diffusion unevenness. The problem.

Method used

By providing a fiber steering device in the solidification bath, the angle between the plane of the solidification fiber tow and the vertical direction is 0° to 10°, and the departure method of the fiber tow is controlled by using the crimping roller set device, combining the spinneret and The design of the curling roller optimizes the guidance and forming process of the fiber tow to reduce the filament breakage phenomenon.

Benefits of technology

The diameter uniformity and mechanical properties of polyacrylonitrile primary fibers are significantly improved, the wool content and elongation of break are reduced, and the comprehensive performance of polyacrylonitrile-based carbon fibers are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119308032A_ABST
    Figure CN119308032A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fibers, in particular to a polyacrylonitrile nascent fiber, a polyacrylonitrile-based carbon fiber and a preparation method thereof. The value of A * B * C * 100 of the polyacrylonitrile nascent fiber is not greater than 30% and is not 0%; wherein A is a monofilament tensile strength CV value of 40 to 100 polyacrylonitrile nascent fibers; b is a monofilament tensile modulus CV value of 40 to 100 polyacrylonitrile nascent fibers; the polyacrylonitrile nascent fiber from leaving the coagulating bath to a first crimping roller in the crimping roller set device is in a contracted state in the transverse direction, C is a width difference value (a1-a2) before and after contraction, the unit is cm, a1 is the width of the polyacrylonitrile nascent fiber leaving the coagulating bath, and a2 is the width of the polyacrylonitrile nascent fiber just in contact with the first crimping roller. By utilizing the polyacrylonitrile nascent fiber, the diameter uniformity of the polyacrylonitrile-based carbon fiber can be obviously influenced, and the mechanical property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fibers, and in particular to polyacrylonitrile primary fibers, polyacrylonitrile-based carbon fibers and preparation methods thereof. Background Art

[0002] Carbon fiber has comprehensive properties such as high tensile strength, high tensile modulus, low density, high temperature resistance, ablation resistance, corrosion resistance, high electrical and thermal conductivity, low thermal expansion, self-lubrication and good biocompatibility. Carbon fiber is widely used in aerospace, automotive industry, construction energy and sports equipment. At present, the world's manufacturers of polyacrylonitrile-based carbon fiber mainly include Japan's Toray, Toho, Mitsubishi Rayon and the United States' Hexcel, Zoltek, etc.

[0003] In May 2011, Hershey Corporation of the United States launched IM10 carbon fiber with a tensile strength of 6964MPa and a tensile modulus of 310PGPa; in March 2014, Toray Corporation of Japan used traditional PAN solution spinning technology to finely control the carbonization process, improve the microstructure of carbon fiber at the nanoscale, and control the orientation, crystallite size, and defects of graphite crystals in carbonized fibers. It developed T1100G carbon fiber with a tensile strength of 6600MPa and a tensile modulus of 324PGPa; in July 2015, Toho Corporation of Japan released the XMS32 new carbon fiber with both high tensile strength and high tensile modulus; in November 2018, Toray Corporation of Japan announced the development of M40X carbon fiber with a tensile strength of 5700MPa and a tensile modulus of 377PGPa. A class of ultra-high strength, medium and high modulus carbon fibers have been developed one after another. The above-mentioned carbon fibers are significantly improved in both tensile strength and tensile modulus than traditional T800 high-strength medium modulus carbon fibers. This type of carbon fiber greatly improves the comprehensive performance of composite parts and has a positive significance in achieving lightweight and high strength of composite materials and carbon fiber efficiency. However, it places extremely high demands on the control of defect structures that affect carbon fibers.

[0004] Polyacrylonitrile (PAN)-based carbon fiber is a kind of artificially synthesized inorganic fiber, which is obtained by pre-oxidation and carbonization of polyacrylonitrile fiber. The mainstream practice in China is to prepare polyacrylonitrile fiber by wet spinning. The preparation of polyacrylonitrile precursor usually adopts oil solvents such as dimethylacetamide, dimethyl sulfoxide (DMSO) or non-polar solvents such as sodium thiocyanate and zinc chloride to make spinning solution. Among them, DMSO has relatively low toxicity and has the characteristics of relatively simple and mature process, so it has been widely used. The high-viscosity spinning solution is successively prepared by multi-stage coagulation forming, hot water drawing, water washing, oiling and drying densification, steam drawing, and relaxation heat setting to obtain polyacrylonitrile fiber. The preparation process of polyacrylonitrile precursor is one of the key technologies for the preparation of carbon fiber. The comprehensive performance of carbon fiber is closely related to the process of precursor preparation, especially the control of precursor process.

[0005] The structure of polyacrylonitrile fiber (carbon fiber precursor fiber) determines the basic structure of polyacrylonitrile-based carbon fiber. In particular, when the internal structure of polyacrylonitrile fiber is uneven, poorly oriented, and has many defects, the performance of polyacrylonitrile-based carbon fiber will be greatly reduced. The spinning solution stream slowly forms a fiber morphology in the coagulation bath and becomes a primary fiber. The primary fiber is the prototype of polyacrylonitrile fiber. The coagulation double diffusion speed is not easy to control during coagulation, and the transformation process of the spinning solution stream in the coagulation bath directly determines the structure of the primary fiber. By improving the spinning solution and coagulation process, it is hoped that the density and homogeneity of the carbon fiber precursor structure will be solved, the quality of the precursor will be improved, and thus the performance of the final carbon fiber will be improved.

[0006] The coagulation process parameters of wet spinning include coagulation bath temperature, concentration and negative draft, etc. In the prior art, the coagulation bath tank is mainly composed of a main tank body, a distribution plate and an overflow plate. When the coagulation process is unreasonable, the newly formed nascent fibers will break under the disturbance of the coagulation liquid flow field. The newly formed nascent fibers are easily broken due to the tensile stretching in the coagulation bath. After the coagulated fibers leave the coagulation bath, they enter the air atmosphere from the liquid environment. The temperature drop and the coagulation tension work together to make the coagulated filaments very easy to break. The above-mentioned different types of inducements can cause the coagulated filaments to be partially broken, forming exposed hair fibers floating outside the main body of the filament bundle, or being clamped inside the filament bundle and carried into the next spinning section; or being completely broken, flowing with the coagulation liquid, and finally enriched at the overflow port. Partially broken filaments are wound around the guide rollers, while completely broken filaments are carried to the overflow port of the coagulation liquid along with the flow of the coagulation liquid, so that a lot of broken filaments are collected in the overflow port of the coagulation bath after a certain period of accumulation. Broken filaments are an important defect of primary fibers, which is inherited and causes an increase in the number of hairy filaments in the raw fibers and a decrease in the mechanical properties of polyacrylonitrile fibers.

[0007] CN112708945A discloses a coagulation bath tank for wet spinning and a method for coagulation molding of polyacrylonitrile spinning stock solution. The method reduces the occurrence of coagulation bath broken wires caused by coagulation liquid impact and temperature difference by setting a fairing around the spinneret and near the coagulation bath tow leaving the liquid surface; overcomes the occurrence of coagulation bath broken wires caused by tension difference by increasing the adjustment of the guide roller in the height direction and the active and passive power adjustment, and eliminates the phenomenon of wire entanglement on the guide roller in the coagulation bath and many broken wires in the overflow tank. However, the fairing will cause the accumulation of solvent content around the tow; it makes it difficult for the coagulating agent to diffuse into the fairing, seriously affecting the double diffusion process of the tow, resulting in poor molding effect of the coagulated fiber.

[0008] CN216039977U discloses a coagulation forming device, which includes a coagulation bath, a spinneret and a guide roller. The lower edge of the roller body of the guide roller can be immersed in the coagulation bath, and the position of the lower edge of the roller body of the guide roller is higher than the position of the spinneret. The device can be used to design the components of the coagulation forming device. Although the device arranges the components reasonably, avoids the phenomenon of fiber hair, broken wire and bifurcation during the coagulation process, and avoids the phenomenon of fiber unevenness caused by the uneven temperature concentration field of the coagulation bath, but the lifting slope of the fiber bundle between the spinneret and the guide roller along the wire running direction is 1 to 5 degrees, which is easy to cause the uneven tension field between the single wires at different positions of the spinneret, thereby causing the generation of broken wires near the spinneret; and the guide roller with the lower edge immersed in the coagulation bath is also very likely to cause the change of the flow field of the fiber bundle near and around the guide roller, resulting in uneven double diffusion and an increase in coagulation broken wires.

[0009] CN114457436A discloses a method for preparing polyacrylonitrile-based carbon fiber precursor, a tow and an application method, wherein a polyacrylonitrile spinning solution with a certain characteristic viscosity is used for spinning, and the method includes the steps of coagulation and drying densification of wet spinning; the method is characterized in that the tow tension Q1 in the coagulation step is Q1=k1×M, wherein k1 is the tension coefficient, k1=0.05-0.40; in the drying densification step, the tow tension Q2=k2×M, k2 is the tension coefficient, wherein k2=0.38-1.10; and M is the number of tow roots. The technical solution solves the problems of a large number of thin filaments and (or) thick filaments in the carbon fiber precursor, uneven distribution of fiber cross-sectional dimensions and poor mechanical properties, and the method can be used in the preparation process of polyacrylonitrile-based carbon fiber precursor. Summary of the invention

[0010] The purpose of the present invention is to provide a new polyacrylonitrile primary fiber, which can be used to prepare a polyacrylonitrile-based carbon fiber with the advantages of low diameter unevenness, low fuzz content, high mechanical properties, and low CV values ​​of tensile strength and elongation at break.

[0011] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a polyacrylonitrile spun fiber, wherein the value of A*B*C*100 is not greater than 30% and is not 0%; wherein A is the CV value of the single-filament tensile strength of 40-100 of the polyacrylonitrile spun fibers; B is the CV value of the single-filament tensile modulus of 40-100 of the polyacrylonitrile spun fibers; the polyacrylonitrile spun fibers are in a contracted state in the transverse direction from leaving the coagulation bath to the first winding roller in the winding roller group device, and C is the width difference before and after contraction (a1-a2), in cm, wherein a1 is the width of the polyacrylonitrile spun fiber leaving the coagulation bath, and a2 is the width of the polyacrylonitrile spun fiber just contacting the first winding roller.

[0012] The second aspect of the present invention provides a method for preparing the polyacrylonitrile primary fiber of the present invention, which adopts wet spinning; the preparation method comprises: the acrylonitrile copolymer spinning stock solution is extruded through a spinneret, coagulated and formed, and then leaves the coagulation bath to obtain the primary fiber; wherein, during coagulation, a fiber steering device is arranged below the coagulation bath liquid surface near the inner side of the coagulation bath outlet so that the angle between the plane of the coagulated fiber bundle coagulated in the coagulation bath and the vertical direction is 0° to 10°, and the fiber steering device and the center position of the spinneret are at the same level; the center point of the first curling roller in the curling roller group device at the upper position of the coagulation bath outlet is controlled to be 10 cm to 150 cm above the coagulation bath liquid surface so that the coagulated fiber bundle coagulated in the coagulation bath leaves the coagulation bath.

[0013] A third aspect of the present invention provides a polyacrylonitrile-based carbon fiber, wherein the value of the breaking strength CV value*breaking elongation CV value*100 of the polyacrylonitrile-based carbon fiber is not greater than 10%.

[0014] The fourth aspect of the present invention provides a method for preparing the polyacrylonitrile-based carbon fiber of the present invention, which comprises: preparing the polyacrylonitrile primary fiber of the present invention, or the polyacrylonitrile primary fiber prepared by the method for preparing the polyacrylonitrile primary fiber of the present invention, drawing, washing, oiling, drying and densification, steam drawing, and heat setting to obtain polyacrylonitrile precursor, and pre-oxidizing and carbonizing the polyacrylonitrile precursor to obtain the polyacrylonitrile-based carbon fiber.

[0015] Through the above technical scheme, the present invention provides a new polyacrylonitrile primary fiber with excellent mechanical CV value. The polyacrylonitrile primary fiber of the present invention can significantly affect the diameter uniformity and mechanical property improvement of polyacrylonitrile-based carbon fiber; and the specific polyacrylonitrile primary fiber of the present invention can be prepared by the preparation method of the present invention. The polyacrylonitrile carbon fiber prepared by using the polyacrylonitrile primary fiber has the advantages of low diameter unevenness, low hair content, high mechanical property, and low CV value of tensile strength and elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the process of preparing polyacrylonitrile primary fiber.

[0017] Figure 2 It is a schematic diagram of the cross-sectional morphology of the nascent polyacrylonitrile fiber from leaving the coagulation bath to the first winding roller.

[0018] Figure 3 This is a schematic diagram of the sampling area for the mechanical properties test of polyacrylonitrile primary fibers in the laboratory.

[0019] Description of Reference Numerals

[0020] 1. Raw liquid delivery pipeline 2. Spinning assembly

[0021] 3. Coagulation of fiber bundles 4. Coagulation bath

[0022] 5. Fiber steering device 6. Polyacrylonitrile primary fiber top

[0023] 7. The first crimping roller 8. The bottom of the polyacrylonitrile primary fiber

[0024] α1 / α / α3, the angle between the plane of the coagulated fiber bundle in the coagulation bath and the vertical direction

[0025] h, the height of the center point of the first winding roller in the winding roller group device of the coagulation bath from the surface of the coagulation bath DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] In the present invention, the test method for the tensile strength CV value, tensile modulus CV value and elongation at break CV value of 40-100 polyacrylonitrile primary fibers is as follows: take the coagulated fibers (i.e., polyacrylonitrile primary fibers) from the time when they leave the coagulation bath to the time when they just touch the first crimping roller, and perform sample pretreatment. Keep the orientation and shape of the taken fibers in order, such as Figure 3 As shown, Figure 3This is a schematic diagram of the sampling area for the mechanical properties test of polyacrylonitrile primary fiber in the laboratory. A small bundle of fibers is selected from the top A area, the top B area, the bottom A area and the bottom B area. The number of single fibers selected in each area is between 100 and 300. The fibers in different areas are marked as uA, uB, dA and dB respectively. Take a 1m long bundle of polyacrylonitrile primary fiber and mark it as S. Soak uA, uB, dA, dB and S in acetone and ethanol for two hours respectively, take them out, dry them naturally for 24 hours, and then test them. Weigh S and use it to calculate the fineness of polyacrylonitrile primary fiber by weighing method. For the mechanical properties of uA, uB, dA and dB test monofilaments, 10-25 monofilaments were selected on average for testing (the fineness data of S was used for the mechanical property testing and calculation of uA, uB, dA and dB), and finally the tensile strength of a total of 40-100 monofilaments was summarized and analyzed, and then the monofilament tensile strength CV value, tensile modulus CV value and elongation at break CV value of 40-100 polyacrylonitrile primary fibers were calculated. The tensile strength CV value, tensile modulus CV value and elongation at break CV value of the monofilaments in the present invention were all tested under the same conditions.

[0028] In the present invention, the test method for the swelling degree of polyacrylonitrile primary fiber is as follows: 10 g of the coagulated fiber (i.e., polyacrylonitrile primary fiber) filaments from the first crimping roller to the surface of the coagulation bath are taken, washed in flowing deionized water for 30 min, and then placed in a centrifugal dehydrator (3000 r / min, 15 min) for dehydration treatment to remove the water attached to the surface of the coagulated filaments and the water sandwiched between the monofilaments, and the weight is weighed as W; then placed in a hot air drying oven at 110°C for 2 h, and then placed in a dryer to cool to room temperature, and the weight is weighed as W0, and the swelling degree BG of the coagulated filaments is calculated according to the following formula, that is,

[0029] Swelling degree BG (%) = (W-W0) / W0×100;

[0030] Where, W is the weight of the coagulated filament itself + the weight of water in the pores of the coagulated filament;

[0031] W0——The weight of the coagulated filament after drying.

[0032] In the present invention, the method for testing the tension of the fiber bundle is as follows: a handheld tension meter (SCHMIDT DTBB series) is used to test the tension of the fiber at each stage of spinning, and tension meters of different ranges are selected according to the specifications of the fiber bundle and the stage of the fiber. Before starting the tension meter, the hair on the guide wheel and the measuring wheel is first removed to ensure that the surface of the guide wheel and the measuring wheel is smooth and free of dirt, and the guide wheel and the measuring wheel can slide easily and without resistance. If necessary, lubricating grease of the specification specified by the tension meter manufacturer is dripped into the gap of the sliding module. After starting, the tension meter is preheated for half an hour; then the "ZERO" button is pressed on the tension meter to clear the data and start the test again. The fiber is clamped on the tension meter, and the fiber bundle passes through the guide wheel 1, the measuring wheel and the guide wheel 2 in sequence. The tension meter is manually controlled to be stable, and the fiber wire running direction is not changed during the measurement stage; the fiber is not twisted, and the tension meter reading is stabilized (tension fluctuation is less than ±10CN), and the tension data is read every 10 seconds. The average value of the three tension data is the tension value of the fiber bundle at this stage.

[0033] In the present invention, the mechanical properties of carbon fiber are measured using GB / T 26752-2011.

[0034] In the present invention, the method for measuring broken fibers at the overflow port of the coagulation bath is as follows: a stainless steel filter screen (material: 316L) with a specification of 400 mesh is set at the overflow port of the coagulation bath to intercept the broken fibers of the coagulated fibers in the coagulation bath. The broken fibers of the coagulated fibers on the stainless steel filter screen are collected every 100 hours of spinning. The collected broken fibers of the coagulated fibers are soaked in acetone for 2 hours; after being fished out, they are soaked in ethanol for 2 hours; after being taken out from the ethanol, they are naturally dried for 2 hours, and finally dried in a blast oven at 80°C for 2 hours. After cooling to room temperature, the mass m of the broken fibers of the coagulated fibers is weighed and expressed in grams (g).

[0035] In the present invention, the method for testing the fuzzing amount of carbon fiber is carried out in accordance with Q / BH enterprise standard Q / 110000BH 006-2018 Carbon fiber tow fuzzing amount test method (issued on July 1, 2018, implemented on August 1, 2018, issued by Beijing University of Aeronautics and Astronautics).

[0036] In the present invention, the test method for the diameter unevenness of polyacrylonitrile-based carbon fiber is as follows: first, a test method for the cross section of the carbon fiber is established. The liquid nitrogen brittle fracture method is used to prepare the carbon fiber cross-section sample, and the carbon fiber bundle after removing the sizing agent is fixed on an aluminum sheet with a flat edge with a conductive double-sided tape. The aluminum sheet with the carbon fiber is inserted into the liquid nitrogen for more than ten seconds, and then the fiber is broken along the edge of the aluminum sheet to obtain the carbon fiber cross-section sample. A scanning electron microscope is used to observe the carbon fiber cross-section sample after the gold spraying treatment. During the experiment, the sample stage is rotated and tilted to ensure that the fiber cross section is facing the field of view, so as to reduce the test error of the fiber cross-section contour caused by projection. Save the photograph (file type: JPEG image, format.jpg) for subsequent analysis.

[0037] Carbon fiber cross-sectional morphology analysis, statistics and processing, Method 1: Use the automatic statistical analysis module of image pro plus software to perform statistical analysis on the cross-sectional morphology characteristics (diameter, area) of 500 to 1000 carbon fibers on the cross-sectional photos of carbon fibers, and obtain the average diameter, diameter size distribution, average cross-sectional area and cross-sectional area distribution of 500 to 1000 carbon fiber cross-sections. The specific steps are as follows: A. Set the intensity of the cross-sectional photos to 65 to remove noise; B. Standardize the histogram of the image obtained by A; C. For the image obtained by B, set the boundary threshold to 130 and perform binarization.

[0038] Carbon fiber cross-sectional morphology analysis, statistics and processing, Method 2: Aiming at the morphological characteristics of the cross section of polyacrylonitrile-based carbon fiber, MATLAB software was used for programming, and the prepared program was used to analyze the saved carbon fiber cross-sectional photos, and the cross-sectional morphological characteristics (diameter, area) of 500 to 1000 fibers on the cross-sectional photos of the carbon fiber were statistically analyzed to obtain the average diameter, diameter size distribution (diameter CV value), average cross-sectional area and cross-sectional area distribution of 500 to 1000 carbon fiber cross-sections. And the relationship curve between the carbon fiber cross-sectional image diameter and the diameter probability density distribution (%), as well as the relationship curve between the carbon fiber cross-sectional image diameter and the cumulative diameter distribution was obtained.

[0039] One of the above methods 1 and 2 is used to analyze the cross-sectional morphology of the carbon fiber to obtain statistical information of the carbon fiber cross-section, including the average diameter, diameter size distribution, average cross-sectional area, cross-sectional area distribution, and the number of anisotropic cross-sectional wires of 500 to 1000 carbon fiber precursors.

[0040] In the above-mentioned analysis method of the cross-sectional morphology of carbon fiber, the number of carbon fiber precursors is counted to be between 500 and 1000.

[0041] The first aspect of the present invention provides a polyacrylonitrile spun fiber, wherein the value of A*B*C*100 is not greater than 30% and is not 0%; wherein A is the CV value of the single-filament tensile strength of 40-100 of the polyacrylonitrile spun fibers; B is the CV value of the single-filament tensile modulus of 40-100 of the polyacrylonitrile spun fibers; the polyacrylonitrile spun fibers are in a contracted state in the transverse direction from leaving the coagulation bath to the first winding roller in the winding roller group device, and C is the width difference before and after contraction (a1-a2), in cm, wherein a1 is the width of the polyacrylonitrile spun fibers leaving the coagulation bath, and a2 is the width of the polyacrylonitrile spun fibers just contacting the first winding roller.

[0042] Polyacrylonitrile primary fibers are used as precursors for preparing polyacrylonitrile carbon fibers. In the present invention, the polyacrylonitrile carbon fibers prepared using polyacrylonitrile primary fibers satisfying A*B*C*100 of not more than 30% and not 0% not only have good high uniformity, but also have excellent mechanical properties.

[0043] According to the present invention, in some preferred embodiments, the value of A*B*C*100 is not greater than 20% and is not 0%, preferably 0.5% to 20%, more preferably 0.5% to 6%, and more preferably 0.5% to 3%. The polyacrylonitrile carbon fiber prepared using the polyacrylonitrile primary fiber of the preferred embodiment not only has good high uniformity, but also has excellent mechanical properties.

[0044] According to the present invention, in some preferred embodiments, A is not higher than 5%, for example, 1%, 1.5%, 2%, 2.4%, 2.5%, 2.9%, 3%, 3.5%, 4.1%, 4.4%, 4.7% or 5%, and the range of any two of the above values, preferably 2% to 3.5%. The polyacrylonitrile carbon fiber prepared using the polyacrylonitrile primary fiber of the preferred embodiment not only has good high uniformity, but also has excellent mechanical properties.

[0045] According to the present invention, in some preferred embodiments, B is not higher than 3%, for example, 0.5%, 1%, 1.3%, 1.5%, 1.6%, 1.9%, 2.2%, 2.6% or 3%, and a range consisting of any two of the above values, preferably 1.5% to 2.5%.

[0046] According to the present invention, in some preferred embodiments, C is 0.2-2.0, for example, 0.2, 0.3, 0.6, 0.8, 1, 1.3, 1.5, 1.6, 1.8 or 2, and a range consisting of any two of the above values, in cm.

[0047] According to the present invention, it can be understood that the polyacrylonitrile primary fiber described in the present invention is prepared by a coagulation molding method, and is guided to subsequent processes by a crimping roller group device.

[0048] According to the present invention, the polyacrylonitrile primary fibers from leaving the coagulation bath to the first curling roller in the curling roller group device present an uneven thickness in the longitudinal direction, wherein the middle area is a flat state with uniform thickness; the two ends are consistently in a circular state, specifically, the middle area is a flat state with uniform thickness and translucent; the two ends are consistently in a white circular state, specifically a circular fiber bundle (or fiber strand).

[0049] like Figure 2 The figure shows the cross-sectional morphology of the polyacrylonitrile nascent fiber from leaving the coagulation bath to the first crimping roller in the crimping roller group device.

[0050] According to the present invention, in some preferred embodiments, the swelling degree of the as-spun fibers is 100% to 180%, preferably 120% to 180%.

[0051] The second aspect of the present invention provides a method for preparing the polyacrylonitrile primary fiber of the present invention, which adopts wet spinning; the preparation method comprises: the acrylonitrile copolymer spinning stock solution is extruded through a spinneret, coagulated and formed, and then leaves the coagulation bath to obtain the primary fiber; wherein, during the coagulation, a fiber steering device is arranged below the coagulation bath liquid surface near the inner side of the coagulation bath outlet so that the angle between the plane of the coagulated fiber bundle coagulated in the coagulation bath and the vertical direction is 0° to 10° (such as Figure 1 α1, α2 and α3 in the figure), the fiber steering device is at the same level as the center position of the spinneret; the height of the center point of the first crimping roller in the crimping roller group device above the outlet side of the coagulation bath is controlled to be 1 / 4 of the height above the coagulation bath liquid surface (as shown in FIG. Figure 1 The distance (shown in h) is 10 cm to 150 cm, so that the coagulated fiber bundle coagulated in the coagulation bath leaves the coagulation bath.

[0052] According to the present invention, "coagulation bath outlet side" refers to the side where the coagulated fiber bundle is ready to leave the coagulation bath. Technicians in this field can adjust the fiber steering device and the curling roller group device according to the angle between the plane of the desired coagulated fiber bundle and the vertical direction of 0° to 10° and the height of the center point of the first curling roller from the coagulation bath liquid surface. Specifically, the fiber steering device is height-adjustable and horizontally movable. The fiber steering device can be arranged on the end plate on the outlet side of the coagulation bath tank, or placed on the bottom of the coagulation bath tank. The height adjustment of the fiber steering device is mainly to match the center position of the fiber steering device and the spinneret at the same level. When it is satisfied, the height is locked, and then the height of the center point of the first curling roller from the coagulation bath liquid surface is adjusted. Finally, the fiber steering device is adjusted by horizontally moving the steering device. The steering device makes the included angle α between the plane of the coagulated fiber bundle and the vertical direction; and it is well known to those skilled in the art that the coagulation bath overflow port is a component of the coagulation bath tank, which is generally arranged on the outlet side of the coagulation bath, that is, during coagulation molding in the present invention, a fiber steering device is arranged below the coagulation bath liquid surface near the inner measure of the coagulation bath overflow port, and the fiber steering device and the center position of the spinneret are at the same level, and a curling roller group device is arranged above the coagulation bath liquid surface near the inner measure of the coagulation bath overflow port, so that the included angle between the plane of the coagulated fiber bundle and the vertical direction is between 0° and 10°; the center point of the first curling roller of the curling roller group device is between 10 cm and 150 cm above the coagulation bath liquid surface, and the coagulation fiber bundle leaves the coagulation bath through the curling roller group device of the coagulation bath.

[0053] In the present invention, the number of primary fibers basically depends on the model selected by the spinneret (e.g., spinneret). Those skilled in the art can select the corresponding spinneret according to their needs, such as a 6K pore size 55um spinneret, a 12K pore size 55um spinneret, a 3K pore size 55um spinneret or a 1K pore size 55um spinneret.

[0054] In the present invention, the plane of the coagulated fiber bundle refers to a plane formed and expanded by the coagulated fiber bundle in the width direction and the bundle running direction.

[0055] In the present invention, it can be understood that the first crimping roller in the crimping roller group device contacts and pulls the coagulated fiber bundle in the coagulation bath after coagulation and forming, so that the coagulated fiber bundle in the coagulation bath leaves the coagulation bath, thereby obtaining the polyacrylonitrile primary fiber.

[0056] In the present invention, the inventors of the present invention have found that in the wet spinning process, by controlling the guidance of the coagulated fiber bundles in the coagulation bath during coagulation and the way the bundles leave the coagulation bath, the polyacrylonitrile primary fibers with the characteristics of A*B*C*100 not greater than 30% and not 0% can be obtained. The use of the polyacrylonitrile primary fibers can better prepare polyacrylonitrile-based carbon fibers with the advantages of low diameter unevenness, low hair content, high mechanical properties, and low CV values ​​of tensile strength and elongation at break.

[0057] According to the present invention, in a preferred embodiment, the center point of the first winding roller in the winding roller group device of the coagulation bath is 20 cm to 50 cm above the coagulation bath liquid level, for example, 20 cm, 30 cm, 35 cm, 40 cm, 45 cm, 20 cm, or a range consisting of any two of the above values. By adopting this preferred embodiment, polyacrylonitrile primary fibers with better structure and performance can be obtained, and polyacrylonitrile primary fibers can be used to prepare polyacrylonitrile carbon fibers with high uniformity and high mechanical properties.

[0058] According to the present invention, in a preferred embodiment, the angle between the plane of the coagulated fiber bundle and the vertical direction is 0° to 5°. Under this preferred embodiment, polyacrylonitrile primary fibers with better structure and performance can be obtained, and polyacrylonitrile carbon fibers with high uniformity and high mechanical properties can be prepared using the polyacrylonitrile primary fibers.

[0059] According to the present invention, in a preferred embodiment, the fiber deflection device is arranged on the end plates on both sides of the coagulation bath, or is placed at the bottom of the coagulation bath.

[0060] According to the present invention, in a preferred embodiment, the fiber deflection device is a passive guide rod, and preferably the bottom surface of the guide rod is at the same level as the center position of the spinneret.

[0061] According to the present invention, in a preferred embodiment, the fiber deflection device is a guide pulley, and preferably the bottom of the guide pulley is at the same level as the center position of the spinneret.

[0062] According to the present invention, in a preferred embodiment, the surface roughness of the fiber steering device is Ra≤0.2; for example, a hard chrome layer with a thickness of 0.02 to 0.08 mm can be plated on the surface of the fiber steering device to make its surface roughness Ra≤0.2. Under this preferred embodiment, polyacrylonitrile primary fibers with better structure and performance can be obtained, and polyacrylonitrile carbon fibers with high uniformity and high mechanical properties can be prepared using the polyacrylonitrile primary fibers.

[0063] According to the present invention, in order to reduce the influence of the fiber steering device on the coagulating fiber bundle, in a preferred embodiment, the fiber steering device is inert in the coagulating liquid, for example, the fiber steering device is made of 304 / 316 / 316L stainless steel, Hastelloy and the like.

[0064] According to the present invention, in a preferred embodiment, the wrap angle between the coagulated fiber bundle and all the curling rollers of the curling roller group device is 360° to 3600°, for example, 360°, 500°, 720°, 1000°, 1440°, 1800°2000°, 2160°, 2520°, 3000°, 3600°, or a range consisting of any two of the above values, preferably 720° to 2520°, and further preferably 1440° to 2160°. Using this embodiment, the prepared polyacrylonitrile primary fiber has better structure and performance, and the use of the polyacrylonitrile primary fiber can prepare polyacrylonitrile carbon fiber with high uniformity and high mechanical properties.

[0065] In the present invention, the wrap angle between the coagulated fiber bundle and all the winding rollers of the winding roller group device refers to the wrap angle between all the winding rollers including the first winding roller and the coagulated fiber bundle, that is, it refers to the ratio of the contact length between the coagulated fiber bundle and all the winding rollers to the cross-sectional radius of the cylindrical winding roller (expressed in radians), and then the ratio expressed in radians is converted into a "°" value.

[0066] The number of the curling rollers in the present invention is not particularly limited, as long as the desired wrap angle is met, and the curling roller can be any curling roller in the art.

[0067] According to the present invention, in a preferred embodiment, the temperature of the coagulated fiber bundle entering the atmosphere after leaving the coagulation bath liquid surface is not higher than the coagulation bath temperature. With this embodiment, the prepared polyacrylonitrile primary fiber has better structure and performance, and the polyacrylonitrile primary fiber can be used to prepare polyacrylonitrile carbon fiber with high uniformity and high mechanical properties.

[0068] According to the present invention, in a particularly preferred embodiment, the difference between the temperature of the coagulation bath and the temperature of the atmosphere into which the coagulated fiber bundle enters after leaving the coagulation bath is 0°C to 15°C, for example, 0°C, 2°C, 3°C, 5°C, 8°C, 10°C, 12°C, 14°C, 15°C, or a range consisting of any two of the above values, preferably 2°C to 10°C, and more preferably 3°C to 8°C. Using this preferred embodiment, the prepared polyacrylonitrile primary fiber has better structure and performance, and the polyacrylonitrile primary fiber can be used to prepare polyacrylonitrile carbon fiber with high uniformity and high mechanical properties.

[0069] In the present invention, the atmosphere that the coagulated fiber bundles enter after leaving the coagulation bath is air, and the temperature of the atmosphere that the coagulated fiber bundles enter after leaving the coagulation bath can be controlled by any conventional means in the art. For example, a sealed cover that can pass hot air is used to cover the coagulation bath and the space that the coagulated fiber bundles enter after leaving the coagulation bath, and hot air of a certain temperature is introduced into the air to make its temperature meet the requirements.

[0070] According to the present invention, in a preferred embodiment, the coagulated fiber bundle is a bundle of uneven thickness in a flat state; it is composed of a plurality of coagulated fiber filaments, for example, 1000 to 12000 coagulated fibers, preferably 1000, 3000, 6000 or 12000 coagulated fiber filaments.

[0071] According to the present invention, in a preferred embodiment, the width of the coagulated fiber bundle is 20 mm to 100 mm.

[0072] According to the present invention, in a preferred embodiment, the average thickness of the coagulated fiber bundle is 0.2 mm to 3.0 mm.

[0073] According to the present invention, in a preferred embodiment, when the coagulated fiber bundle is composed of 1000 coagulated fiber filaments, the coagulated fiber bundle is a flat bundle with uneven thickness, the width of the coagulated fiber bundle is between 20 mm and 30 mm; the average thickness of the coagulated fiber bundle is between 0.2 mm and 1.0 mm.

[0074] According to the present invention, in a preferred embodiment, when the coagulated fiber bundle is composed of 3000 coagulated fibers, the coagulated fiber bundle is a flat bundle with uneven thickness, the width of the coagulated fiber bundle is between 25 mm and 40 mm; the average thickness of the coagulated fiber bundle is between 0.5 mm and 1.5 mm.

[0075] According to the present invention, in a preferred embodiment, when the coagulated fiber bundle is composed of 6000 coagulated fiber filaments, the coagulated fiber bundle is a flat bundle with uneven thickness, the width of the coagulated fiber bundle is between 30 mm and 60 mm; the average thickness of the coagulated fiber bundle is between 0.5 mm and 2.0 mm.

[0076] According to the present invention, in a preferred embodiment, when the coagulated fiber bundle is composed of 12,000 coagulated fiber filaments, the coagulated fiber bundle is a flat bundle with uneven thickness, the width of the coagulated fiber bundle is between 50 mm and 100 mm, and the average thickness of the coagulated fiber bundle is between 1.0 mm and 3.0 mm.

[0077] According to the present invention, the acrylonitrile copolymer spinning solution can be any acrylonitrile copolymer spinning solution in the art, and the present invention has no special limitation on this. It can be obtained from the market, or prepared by any conventional preparation method in the art. For example, in one embodiment, the acrylonitrile copolymer spinning solution contains polyacrylonitrile copolymer and polar aprotic solvent.

[0078] According to the present invention, preferably, the acrylonitrile copolymer spinning solution contains 18 wt% to 22 wt% of polyacrylonitrile copolymer and 78 wt% to 82 wt% of polar aprotic solvent.

[0079] According to the present invention, preferably, the polyacrylonitrile copolymer is a copolymer of acrylonitrile, comonomer 1 and optionally comonomer 2, comonomer 1 is selected from itaconic acid, and comonomer 2 is selected from at least one of acrylic acid, methyl acrylate, methyl methacrylate, ethyl methacrylate, isobutyl acrylic acid, β-butyl itaconate, mesaconic acid, 2-butenoic acid, maleic acid, methylmaleic acid, acrylamide, acrylamide oxime, hydroxyethyl acrylonitrile, α-chloroacrylonitrile and diacetone acrylamide.

[0080] According to the present invention, preferably, the mass content of the acrylonitrile segment in the polyacrylonitrile copolymer is not less than 96 wt %, preferably 97-99.5 wt %.

[0081] In the present invention, optional means that comonomer 2 may be present or absent.

[0082] According to the present invention, preferably, the weight average molecular weight of the polyacrylonitrile copolymer is 55,000-90,000 g / mol.

[0083] According to the present invention, the acrylonitrile copolymer spinning solution can be obtained from the market or can be prepared by oneself. In a preferred embodiment, the preparation method of the acrylonitrile copolymer spinning solution comprises: feeding acrylonitrile (AN) and itaconic acid (IA) which have been distilled under atmospheric pressure in a mass ratio of 97.5:2.5, with a solid content of 78wt% to 82wt%, azobisisobutyronitrile (AIBN) as an initiator accounting for 0.3wt% to 0.4wt% of the mass percentage of the comonomer, adding dimethyl sulfoxide (DMSO) as a solvent into a reactor, reacting at a constant temperature of 60°C for 22 hours under nitrogen protection to obtain a binary acrylonitrile copolymer spinning solution; then, after the spinning solution is decompressed to remove residual monomers and bubbles, it is filtered through a 2μm filter material to obtain an acrylonitrile copolymer spinning solution. The molecular weight was tested by Ubbelohde viscometer for the viscosity average molecular weight of polyacrylonitrile, and the viscosity was tested by RHEOLab QC viscometer produced by Anton Paar. The molecular weight was around 84,000, the molecular weight distribution was around 3.65, and the viscosity was at 60°C and 10s-1 The lower one is around 72 Pa·s.

[0084] According to the present invention, in a preferred embodiment, the number of the coagulation baths is 1-4 levels.

[0085] According to the present invention, in a preferred embodiment, the coagulation bath comprises: a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath. The spinning stream is coagulated and formed in the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath in sequence, and then leaves the coagulation bath to obtain the primary fiber.

[0086] According to the present invention, in a preferred embodiment, the temperature of the coagulation bath is 35-80°C.

[0087] According to the present invention, in a particularly preferred embodiment, the temperature of the primary coagulation bath is 35-45°C.

[0088] According to the present invention, in a particularly preferred embodiment, the temperature of the secondary coagulation bath is 50-55°C.

[0089] According to the present invention, in a particularly preferred embodiment, the temperature of the three-stage coagulation bath is 70-80°C.

[0090] According to the present invention, the coagulation bath liquid in the coagulation bath can be any one in the art. In a preferred embodiment, the coagulation bath liquid in the coagulation bath comprises: dimethyl sulfoxide and water.

[0091] According to the present invention, in a preferred embodiment, the concentration of the coagulation bath is not less than 10 wt %, that is, the concentration of dimethyl sulfoxide.

[0092] According to the present invention, in a particularly preferred embodiment, the concentration of the coagulation bath liquid in the primary coagulation bath is 65-78 wt %.

[0093] According to the present invention, in a particularly preferred embodiment, the concentration of the coagulation bath liquid in the secondary coagulation bath is 35-50 wt %.

[0094] According to the present invention, in a particularly preferred embodiment, the concentration of the coagulation bath liquid in the three-stage coagulation bath is 15-20 wt %.

[0095] In the present invention, the temperature is adjusted by the circulation flow rate of the coagulation bath; and the concentration of the coagulation bath liquid is adjusted by the water replenishment amount.

[0096] According to the present invention, in a particularly preferred embodiment, the draft ratio of the primary coagulation bath is 0.6-1.0.

[0097] According to the present invention, in a particularly preferred embodiment, the draft ratio of the secondary coagulation bath is 1.0-1.1.

[0098] According to the present invention, in a particularly preferred embodiment, the draft ratio of the three-stage coagulation bath is 1.05-1.30.

[0099] According to the present invention, in a preferred embodiment, Figure 1 As shown, it is a schematic diagram of the process of preparing polyacrylonitrile primary fiber. The method of preparing polyacrylonitrile primary fiber by wet spinning includes:

[0100] The acrylonitrile copolymer spinning stock solution enters the spinneret assembly 2 through the stock solution delivery pipeline 1, and the spinning fine flow after being extruded by the spinneret assembly 2 enters the coagulation bath tank 4 filled with coagulation bath liquid for coagulation and molding treatment to obtain a coagulated fiber bundle 3, and the fiber steering device 5 arranged below the liquid level of the coagulation bath near the overflow port of the coagulation bath is used to adjust the angle between the plane of the coagulated fiber bundle 3 and the vertical direction to be α, and the center point of the first winding roller 7 in the winding roller group device of the coagulation bath is controlled to be at a height h from the coagulation bath liquid level so that the coagulated fiber bundle coagulated and molded in the coagulation bath leaves the coagulation bath to obtain polyacrylonitrile primary fiber, which is flat and has a polyacrylonitrile primary fiber top 6 and a polyacrylonitrile primary fiber bottom 8.

[0101] A third aspect of the present invention provides a polyacrylonitrile-based carbon fiber, wherein the value of the breaking strength CV value*breaking elongation CV value*100 of the polyacrylonitrile-based carbon fiber is not greater than 10%.

[0102] The polyacrylonitrile-based carbon fiber provided by the invention has excellent uniformity and mechanical properties.

[0103] According to the present invention, in a preferred embodiment, the value of the breaking strength CV value * breaking elongation CV value * 100 of the polyacrylonitrile-based carbon fiber is 2 to 10%, for example, 2%, 3%, 3.3%, 4.4%, 4.6%, 5.8%, 6.7%, 7.3%, 8.7%, 9%, 3.3%, or a range consisting of any two of the above values, preferably 3 to 9%, and more preferably 3 to 6%. The polyacrylonitrile-based carbon fiber of this preferred embodiment has good uniformity and improved mechanical properties.

[0104] According to the present invention, in a particularly preferred embodiment, the breaking strength CV value of the polyacrylonitrile-based carbon fiber is not more than 6%, for example, 1%, 1.9%, 2%, 2.2%, 2.5%, 2.8%, 2.9%, 3%, 3.1%, 4%, 5%, or a range consisting of any two of the above values, preferably 1-5%, more preferably 1-3%, and more preferably 1-2.5%.

[0105] According to the present invention, in a particularly preferred embodiment, the elongation at break CV value of the polyacrylonitrile-based carbon fiber is not more than 6%, for example, 1%, 1.5%, 1.9%, 2.3%, 2.5%, 2.8%, 3%, 4%, 5%, or a range consisting of any two of the above values, preferably 1 to 5%, more preferably 1 to 3%.

[0106] According to the present invention, in a particularly preferred embodiment, the diameter CV value of the polyacrylonitrile-based carbon fiber is not greater than 5%, for example, 1%, 1.7%, 2%, 2.4%, 2.7%, 3.1%, 4%, 5%, or a range consisting of any two of the above values, preferably 1 to 5%, and more preferably 1 to 3%.

[0107] According to the present invention, in a particularly preferred embodiment, the breaking strength of the polyacrylonitrile-based carbon fiber is not less than 5.8 GPa, for example, 5.8 Gpa, 5.9 Gpa, 6 Gpa, 6.2 Gpa, 6.4 Gpa, 6.5 Gpa, or a range consisting of any two of the above values, preferably 5.8-6.5 GPa.

[0108] According to the present invention, in a particularly preferred embodiment, the tensile modulus of the polyacrylonitrile-based carbon fiber is not less than 290 GPa, for example, 290 Gpa, 292 Gpa, 294 Gpa, 296 Gpa, 297 Gpa, 299 Gpa, 301 Gpa, 302 Gpa, 303 Gpa, 305 Gpa, or a range consisting of any two of the above values, preferably 290-305 GPa.

[0109] According to the present invention, in a particularly preferred embodiment, the elongation at break of the polyacrylonitrile-based carbon fiber is 1 to 3%, for example, 1%, 1.3%, 1.5%, 1.7%, 1.8%, 2%, 2.1%, 2.5%, 3%, or a range consisting of any two of the above values, preferably 1.5 to 2.5%.

[0110] According to the present invention, in a particularly preferred embodiment, the diameter of the polyacrylonitrile-based carbon fiber is 4.5 um to 7.5 um.

[0111] According to the present invention, in a particularly preferred embodiment, the filament content of the polyacrylonitrile-based carbon fiber with an average diameter of 5.1 um to 5.2 um and a length of 100 m is not more than 40 mg, preferably 15 mg to 40 mg.

[0112] The fourth aspect of the present invention provides a method for preparing the polyacrylonitrile-based carbon fiber of the present invention, which comprises: preparing the polyacrylonitrile primary fiber of the present invention, or the polyacrylonitrile primary fiber prepared by the method for preparing the polyacrylonitrile primary fiber of the present invention, drawing, washing, oiling, drying and densification, steam drawing, and heat setting to obtain polyacrylonitrile precursor, and pre-oxidizing and carbonizing the polyacrylonitrile precursor to obtain the polyacrylonitrile-based carbon fiber.

[0113] According to the present invention, the methods of stretching, washing, oiling, drying and densification, steam stretching and heat setting can be carried out in a conventional manner in the art.

[0114] According to the present invention, in one embodiment, the stretching and washing method includes: polyacrylonitrile primary fiber is subjected to three hot water stretchings, the hot water stretching temperatures are 88-92°C, 95-99°C and 98-99°C, the three hot water stretching ratios may be the same or different, and the total stretching ratio is controlled to be 4.2; the tension of the hot water stretched filament bundle needs to be controlled between 350cN and 700cN; after the hot water stretching, the filaments are subjected to 6 water washings, using a step-by-step heating method, and a stretching of less than 10% is implemented in the washing stage, and the washing temperatures are 40-50°C, 45-55°C, 50-60°C, 55-65°C, 65-75°C and 75-80°C, respectively, and the tension of the washed filament bundle needs to be controlled between 500cN and 700cN.

[0115] According to the present invention, in one embodiment, the method of oiling and drying densification includes: the washed polyacrylonitrile primary fiber enters the first oiling process, the mass concentration of the oil is 2-3%, the temperature is room temperature, the excess oil is squeezed by the squeezing roller, and then enters the first drying densification process; then the second oiling process is performed, the mass concentration of the oil is 1-2%, the temperature is room temperature, the excess oil is squeezed by the squeezing roller, and then enters the second drying densification process; the first drying densification temperature is 90-110°C, the duration is 40-80s; the second drying densification temperature is 110-140°C, the duration is 40-80s

[0116] According to the present invention, in one embodiment, the method of steam drawing and heat setting comprises: steam drawing and heat setting the dried and densified polyacrylonitrile primary fiber, the saturated steam drawing pressure is 0.2-0.4 MPa, the heat setting pressure is 0.15-0.25 MPa, the steam drawing multiple is 2-4; the heat setting multiple is 0.9-0.98; after heat setting, the polyacrylonitrile raw fiber is obtained

[0117] According to the present invention, in one embodiment, the method of pre-oxidation and carbonization treatment includes: pre-oxidation of polyacrylonitrile precursor in five air heat stabilization furnaces, the temperatures are 210-220°C, 220-230°C, 225-230°C, 250-255°C and 265-270°C, respectively, the operating time in each pre-oxidation furnace is 8-15 minutes, the total heat treatment time is 40-80 minutes, and the total draft ratio of pre-oxidation is 10-15%; carbonization is carried out in a nitrogen atmosphere, the temperature of low-temperature carbonization is 380-390°C, the time is 2.5-3min, the draft ratio is 2-4%, the temperature of high-temperature carbonization is 1300-1400°C, the time is 2.5-3min, the draft ratio is -2-3%, and polyacrylonitrile-based carbon fiber is obtained after carbonization.

[0118] The present invention will be described in detail below through examples.

[0119] Example 1

[0120] (1) Acrylonitrile copolymer spinning solution:

[0121] Acrylonitrile (AN) and itaconic acid (IA) which have been distilled at atmospheric pressure are added in a mass ratio of 97.5:2.5, with a solid content of 20.5%, azobisisobutyronitrile (AIBN) as an initiator accounting for 0.35wt% of the mass percentage of the copolymer monomer, and dimethyl sulfoxide (DMSO) is added into a reactor as a solvent, and reacted at a constant temperature of 60°C for 22 hours under nitrogen protection to obtain a binary acrylonitrile copolymer spinning solution; then the spinning solution is decompressed to remove residual monomers and bubbles, and then filtered through a 2μm filter material to obtain an acrylonitrile copolymer spinning solution; the molecular weight is tested for the viscosity-average molecular weight of polyacrylonitrile using an Ubbelohde viscometer, and the viscosity is tested using a RHEOLab QC viscometer produced by Anton Paar. After testing, the molecular weight is 84,000, the molecular weight distribution is 3.65, and the viscosity is 60°C, 10s -1 The lower one is 72Pa·s.

[0122] (2) Solidification molding:

[0123] like Figure 1 As shown, the acrylonitrile copolymer spinning stock solution is metered by a metering pump and filtered again by a 1um filter material, and then enters the spinneret assembly 2 through a stock solution delivery pipeline 1. The spinning fine stream extruded by the spinneret assembly 2 (using a 6K pore size 55um spinneret) enters a coagulation bath tank 4 filled with a coagulation bath liquid for coagulation molding treatment. The extrusion temperature is 60°C, and there are three levels of coagulation baths (the coagulation bath liquid is an aqueous solution of dimethyl sulfoxide). The coagulation bath temperatures are 40°C, 55°C and 75°C, and the concentrations are 69%, 36% and 10% respectively. The circulation flow rate of the coagulation bath is 3m 3 / h、6m3 / h、10m 3 / h, the water replenishment amount was 100L / h, 180L / h, and 300L / h respectively; the draft ratios of coagulation molding were 0.66, 1.0, and 1.2 respectively, and polyacrylonitrile primary fibers were obtained;

[0124] In the coagulation bath, the coagulated fiber bundle 3 in the coagulation bath is a bundle of uneven thickness in a flat state, and the plane of the coagulated fiber bundle 3 refers to the plane formed and expanded by the coagulated fiber bundle 3 in the width direction and the bundle running direction; a wet spinning coagulation bath tank is adopted, and a fiber steering device 5 is arranged below the coagulation bath liquid surface near the inner side of the coagulation bath overflow port; a curling roller group device is arranged above the coagulation bath liquid surface near the inner side of the coagulation bath overflow port; so that the coagulated fiber bundle 3 The angle between the plane and the vertical direction is 5°; the center point of the first curling roller 7 of the curling roller group device is at a height h of 30 cm from the coagulation bath liquid surface; the temperature of the atmosphere entered by the coagulated fiber bundle 3 after leaving the coagulation bath is lower than the coagulation bath temperature, and the difference between the two is maintained between 5°C and 8°C during the spinning process; the wrap angle between the coagulated fiber bundle 3 and the curling roller of the curling roller group device is 1800°; the width of the coagulated fiber bundle 3 is 45 mm, and the average thickness is 1.0 mm.

[0125] The fiber steering device 5 is a passive stainless steel wire rod, which is fixed on the end plates on both sides of the coagulation bath 4. The stainless steel wire rod is at the same level as the center of the spinneret. The material of the wire rod is inert in the coagulation liquid. The surface of the wire rod in contact with the fiber is plated with hard chrome, with a thickness of 0.05 mm and a surface roughness of Ra≤0.2.

[0126] (3) Drafting and washing:

[0127] The polyacrylonitrile primary fiber is subjected to three hot water drawing processes, the hot water drawing temperatures are 90°C, 97°C and 99°C, the three hot water drawing ratios are 1.3, 1.5 and 2.2 respectively, and the total drawing ratio is controlled to be about 4.2; the tension of the hot water drawn tow is controlled between 350cN and 700cN; after the hot water drawing, the filaments are subjected to six water washing processes, and the step-by-step temperature increase method is adopted. The drawing is less than 10% in the water washing stage, and the water washing temperatures are 45°C, 50°C, 55°C, 60°C, 70°C and 80°C respectively, and the tension of the washed tow needs to be controlled to be around 650cN;

[0128] (4) Oiling and drying for densification:

[0129] The washed polyacrylonitrile virgin fiber enters the first oiling process with an oil concentration of 2.5% and a room temperature. The excess oil is squeezed by an extrusion roller and then enters the first drying and densification process. Then, the second oiling process is carried out with an oil concentration of 1.5% and a room temperature. The excess oil is squeezed by an extrusion roller and then enters the second drying and densification process. The first drying and densification process is carried out at a temperature of 100°C and a duration of 60s. The second drying and densification process is carried out at a temperature of 130°C and a duration of 60s.

[0130] (5) Steam drawing and heat setting:

[0131] The dried and densified polyacrylonitrile primary fibers were steam drawn and heat set, the saturated steam drawing pressure was 0.3MPa, the heat setting pressure was 0.2MPa, the steam drawing multiple was 3, and the heat setting multiple was 0.95; after heat setting, polyacrylonitrile precursor fibers were obtained, and the fineness of the polyacrylonitrile precursor fibers was 0.90dtex;

[0132] (6) Pre-oxidation and carbonization:

[0133] The polyacrylonitrile precursor was pre-oxidized in five air heat stabilization furnaces at temperatures of 215°C, 225°C, 228°C, 252°C and 267°C, respectively. The operating time in each pre-oxidation furnace was 11 min, the total heat treatment time was 55 min, and the total stretching ratio of pre-oxidation was 12%. Carbonization was carried out in a nitrogen atmosphere. The low-temperature carbonization temperature was 385°C, the time was 2.8 min, the stretching ratio was 3%, the high-temperature carbonization temperature was 1360°C, the time was 2.8 min, and the stretching ratio was -2.5%. Polyacrylonitrile-based carbon fiber was obtained after carbonization.

[0134] The swelling degree of the prepared polyacrylonitrile spun fibers is 167%, the tensile strength CV value is 2.9%, the tensile modulus CV value is 1.5%, the elongation at break CV value is 2.2%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller 7 is 0.4 cm.

[0135] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 0.6375 g.

[0136] The average diameter of polyacrylonitrile-based carbon fiber is 5.1um; the diameter unevenness value expressed by the diameter CV value is 2.2%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 26mg; the mechanical properties of carbon fiber are as follows: breaking strength 6.0GPa, breaking strength CV value 2.0%; tensile modulus 296GPa, elongation at break 1.9%; elongation at break CV value is 2.3%.

[0137] Example 2

[0138] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0139] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0140] In the coagulation bath, there are three levels of coagulation bath, the coagulation bath temperature is 40℃, 55℃ and 75℃, the concentration is 69%, 36% and 10% respectively, and the circulation flow rate of the coagulation bath is 6m 3 / h、10m 3 / h、22m 3 / h, and the water replenishment amounts are 220L / h, 300L / h, and 700L / h respectively; the draft ratios of solidification molding are 0.66, 1.0, and 1.2 respectively, and a 12K spinneret with an aperture of 55um is used.

[0141] The width of the coagulated fiber tow was 70 mm and the average thickness was 1.2 mm.

[0142] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 169%, the CV value of tensile strength is 3%, the CV value of tensile modulus is 1.6%, the CV value of elongation at break is 2.4%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.6 cm.

[0143] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.3558 g.

[0144] The average diameter of polyacrylonitrile-based carbon fiber is 5.0um; the diameter unevenness value expressed by the diameter CV value is 2.4%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 34mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.9GPa, breaking strength CV value 2.3%; tensile modulus 294GPa, elongation at break 1.7%; elongation at break CV value is 2.5%.

[0145] Example 3

[0146] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0147] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0148] In the coagulation bath, there are three levels of coagulation bath, the coagulation bath temperature is 40℃, 55℃ and 75℃, the concentration is 69%, 36% and 10% respectively, and the circulation flow rate of the coagulation bath is 2m 3 / h、4m 3 / h、5m 3 / h, and the water replenishment amounts are 60L / h, 100L / h, and 180L / h respectively; the draft ratios of solidification molding are 0.66, 1.0, and 1.2 respectively, and a 3K spinneret with an aperture of 55um is used.

[0149] The width of the coagulated fiber tow was 30 mm and the average thickness was 0.6 mm.

[0150] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 165%, the CV value of the tensile strength is 3.5%, the CV value of the tensile modulus is 1.9%, the CV value of the elongation at break is 2.6%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.3 cm.

[0151] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 0.5125 g.

[0152] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 2.7%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 25mg; the mechanical properties of carbon fiber are as follows: breaking strength 6.2GPa, breaking strength CV value 1.9%; tensile modulus 299GPa, elongation at break 2.1%; elongation at break CV value is 2.3%.

[0153] Example 4

[0154] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0155] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0156] In the coagulation bath, there are three levels of coagulation bath, the coagulation bath temperature is 40℃, 55℃ and 75℃, the concentration is 69%, 36% and 10% respectively, and the circulation flow rate of the coagulation bath is 0.8m 3 / h、1.2m 3 / h、1.5m 3 / h, and the water replenishment amounts were 15L / h, 30L / h, and 55L / h respectively; the draft ratios for solidification molding were 0.66, 1.0, and 1.2 respectively, and a 1K spinneret with an aperture of 55um was used.

[0157] The width of the coagulated fiber tow was 25 mm and the average thickness was 0.4 mm.

[0158] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 163%, the CV value of the tensile strength is 2.8%, the CV value of the tensile modulus is 1.3%, the CV value of the elongation at break is 2.1%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.3 cm.

[0159] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 0.3352 g.

[0160] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 3.1%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 19mg; the mechanical properties of carbon fiber are as follows: breaking strength 6.4GPa, breaking strength CV value 2.2%; tensile modulus 297GPa, elongation at break 2.0%; elongation at break CV value is 1.5%.

[0161] Example 5

[0162] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0163] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0164] In the coagulation bath, the angle between the plane of the coagulated fiber bundle and the vertical direction is 2°; the center point of the first winding roller of the winding roller group device is 35 cm above the coagulation bath liquid surface. The temperature of the atmosphere that the coagulation bath bundle enters after leaving the coagulation bath is lower than the coagulation bath temperature, and the difference between the two is maintained between 3°C and 5°C during the spinning process.

[0165] The width of the coagulated fiber tow was 45 mm and the average thickness was 1.1 mm.

[0166] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 159%, the CV value of the tensile strength is 2.4%, the CV value of the tensile modulus is 1.1%, the CV value of the elongation at break is 1.8%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.3 cm.

[0167] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 0.5542 g.

[0168] The average diameter of polyacrylonitrile-based carbon fiber is 5.5um; the diameter unevenness value expressed by the diameter CV value is 1.7%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 22mg; the mechanical properties of carbon fiber are as follows: breaking strength 6.2GPa, breaking strength CV value 1.9%; tensile modulus 296GPa, elongation at break 1.8%; elongation at break CV value is 1.9%.

[0169] Example 6

[0170] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0171] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0172] In the coagulation bath, the angle between the plane of the coagulated fiber bundle and the vertical direction is 9°; the center point of the first winding roller of the winding roller group device is 45 cm above the coagulation bath liquid surface; the wrap angle between the coagulated fiber bundle and the winding roller of the winding roller group device is 2160°.

[0173] The coagulated fiber tow had a width of 45 mm and an average thickness of 1.0 mm.

[0174] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 168%, the CV value of the tensile strength is 3.5%, the CV value of the tensile modulus is 1.9%, the CV value of the elongation at break is 2.4%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.8 cm.

[0175] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 0.7197 g.

[0176] The average diameter of polyacrylonitrile-based carbon fiber is 5.8um; the diameter unevenness value expressed by the diameter CV value is 2.5%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 39mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.9GPa, breaking strength CV value 2.8%; tensile modulus 301GPa, elongation at break 2.2%; elongation at break CV value is 2.4%.

[0177] Example 7

[0178] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0179] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0180] The center point of the first winding roller of the winding roller assembly device is 15 cm above the coagulation bath liquid level.

[0181] The width of the coagulated fiber tow was 53 mm and the average thickness was 1.2 mm.

[0182] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 170%, the CV value of the tensile strength is 4.1%, the CV value of the tensile modulus is 2.2%, the CV value of the elongation at break is 2.6%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 1.3 cm.

[0183] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.2533 g.

[0184] The average diameter of polyacrylonitrile-based carbon fiber is 5.3um; the diameter unevenness value expressed by the diameter CV value is 2.4%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 35mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.8GPa, breaking strength CV value 2.9%; tensile modulus 295GPa, elongation at break 2.4%; elongation at break CV value is 2.5%.

[0185] Example 8

[0186] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0187] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0188] The center point of the first winding roller of the winding roller assembly device is 100 cm above the coagulation bath liquid level.

[0189] The width of the coagulated fiber tow was 44 mm and the average thickness was 1.2 mm.

[0190] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 171%, the CV value of tensile strength is 3.8%, the CV value of tensile modulus is 2.6%, the CV value of elongation at break is 2.3%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.6 cm.

[0191] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.1274 g.

[0192] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 2.0%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 30mg; the mechanical properties of carbon fiber are as follows: breaking strength 6.0GPa, breaking strength CV value 2.3%; tensile modulus 293GPa, elongation at break 1.9%; elongation at break CV value is 2.5%.

[0193] Example 9

[0194] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0195] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0196] The center point of the first winding roller of the winding roller assembly device is 140 cm above the coagulation bath liquid level.

[0197] The width of the coagulated fiber tow was 39 mm and the average thickness was 1.3 mm.

[0198] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 173%, the CV value of the tensile strength is 3%, the CV value of the tensile modulus is 1.9%, the CV value of the elongation at break is 2.4%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 1.6 cm.

[0199] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.2874 g.

[0200] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 2.6%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 36mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.9GPa, breaking strength CV value 3.1%; tensile modulus 294GPa, elongation at break 2.0%; elongation at break CV value is 2.8%.

[0201] Example 10

[0202] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0203] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0204] The temperature of the atmosphere into which the coagulated fiber bundle enters after leaving the coagulation bath is lower than the temperature of the coagulation bath, and the difference between the two is maintained between 12°C and 14°C during the spinning process.

[0205] The width of the coagulated fiber tow was 45 mm and the average thickness was 1.1 mm.

[0206] The prepared polyacrylonitrile spun fibers (coagulated fiber bundles) have a degree of swelling of 168%, a tensile strength CV value of 4.7%, a tensile modulus CV value of 1.3%, a break elongation CV value of 2%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0.9 cm.

[0207] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.1356 g.

[0208] The average diameter of polyacrylonitrile-based carbon fiber is 5.1um; the diameter unevenness value expressed by the diameter CV value is 2.8%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 32mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.8GPa, breaking strength CV value 2.6%; tensile modulus 295GPa, elongation at break 2.0%; elongation at break CV value is 2.8%.

[0209] Embodiment 11

[0210] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0211] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0212] The wrap angle between the coagulated fiber bundle and the crimping roller of the crimping roller assembly device is 3360°.

[0213] The width of the coagulated fiber tow was 55 mm and the average thickness was 1.4 mm.

[0214] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 166%, the CV value of the tensile strength is 4.4%, the CV value of the tensile modulus is 2.6%, the CV value of the elongation at break is 2.8%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 1.5 cm.

[0215] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.2795 g.

[0216] The average diameter of polyacrylonitrile-based carbon fiber is 5.1um; the diameter unevenness value expressed by the diameter CV value is 2.9%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 24mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.9GPa, breaking strength CV value 2.5%; tensile modulus 297GPa, elongation at break 2.1%; elongation at break CV value is 2.9%.

[0217] Comparative Example 1

[0218] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0219] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0220] In the coagulation bath, the angle between the plane of the coagulated fiber bundle and the vertical direction is 70°.

[0221] The width of the coagulated fiber tow was 65 mm and the average thickness was 0.8 mm.

[0222] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 185%, the CV value of the tensile strength is 6.9%, the CV value of the tensile modulus is 5.8%, the CV value of the elongation at break is 7.2%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 2.2 cm.

[0223] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 2.5815 g.

[0224] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 5.9%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 90mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.2GPa, breaking strength CV value 9.5%; tensile modulus 286GPa, elongation at break 1.9%; elongation at break CV value is 10.4%.

[0225] Comparative Example 2

[0226] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0227] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0228] The center point of the first crimping roller of the crimping roller assembly device is 2 cm above the coagulation bath liquid surface; the wrap angle between the coagulated fiber bundle and the crimping roller of the crimping roller assembly device is 2160°.

[0229] The width of the coagulated fiber tow was 70 mm and the average thickness was 0.75 mm.

[0230] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 174%, the CV value of the tensile strength is 8.3%, the CV value of the tensile modulus is 6.6%, the CV value of the elongation at break is 7.6%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 2.5 cm.

[0231] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 3.3975 g.

[0232] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 7.5%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 85mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.1GPa, breaking strength CV value 7.4%; tensile modulus 288GPa, elongation at break 2.0%; elongation at break CV value is 10.6%.

[0233] Comparative Example 3

[0234] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0235] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0236] In the coagulation bath, the first winding roller of the winding roller assembly is immersed below the coagulation bath liquid level.

[0237] The coagulated fiber tow had a width of 45 mm and an average thickness of 1.0 mm.

[0238] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 176%, the CV value of the tensile strength is 5.7%, the CV value of the tensile modulus is 4.7%, the CV value of the elongation at break is 4.8%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 0 cm.

[0239] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 4.3758 g.

[0240] The average diameter of polyacrylonitrile-based carbon fiber is 5.1um; the diameter unevenness value expressed by the diameter CV value is 6.3%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 58mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.1GPa, breaking strength CV value 11.3%; tensile modulus 276GPa, elongation at break 2.0%; elongation at break CV value is 10.3%.

[0241] Comparative Example 4

[0242] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0243] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0244] The center point of the first winding roller of the winding roller group device is 250 cm above the coagulation bath liquid surface; after the coagulation bath filament bundle leaves the coagulation bath and enters the air, the temperature difference between the coagulation bath liquid and the air atmosphere is not controlled. The temperature of the atmosphere entered by the coagulation fiber bundle after leaving the coagulation bath is lower than the coagulation bath temperature, and the difference between the two is between 15°C and 18°C.

[0245] The coagulated fiber tow had a width of 28 mm and an average thickness of 3.0 mm.

[0246] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 179%, the CV value of tensile strength is 5.9%, the CV value of tensile modulus is 4.3%, the CV value of elongation at break is 3.6%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 3.2 cm.

[0247] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 2.8759 g.

[0248] The average diameter of polyacrylonitrile-based carbon fiber is 5.2um; the diameter unevenness value expressed by the diameter CV value is 6.8%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 74mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.2GPa, breaking strength CV value 8.5%; tensile modulus 285GPa, elongation at break 1.9%; elongation at break CV value is 9.6%.

[0249] Comparative Example 5

[0250] The contents of steps (1), (3), (4), (5), and (6) are exactly the same as the corresponding contents in Example 1;

[0251] Part of the content of step (2) is exactly the same as the corresponding content of Example 1, and the different contents are listed as follows:

[0252] The stainless steel wire guide rod is higher than the center of the spinneret, with a height difference of 10 cm.

[0253] The coagulated fiber tow had a width of 45 mm and an average thickness of 1.0 mm.

[0254] The degree of swelling of the prepared polyacrylonitrile spun fibers (coagulated fiber bundles) is 169%, the CV value of tensile strength is 6.2%, the CV value of tensile modulus is 3.9%, the CV value of elongation at break is 4.5%, and the width difference between the width a1 of the polyacrylonitrile spun fibers leaving the coagulation bath and the width a2 of the polyacrylonitrile spun fibers just contacting the first winding roller is 2.2 cm.

[0255] Every 100 hours of spinning, the amount of broken fibers in the coagulation bath at the overflow port of the first coagulation bath of wet spinning was 1.9856 g.

[0256] The average diameter of polyacrylonitrile-based carbon fiber is 5.1um; the diameter unevenness value expressed by the diameter CV value is 8.2%; the apparent content of 100m length of polyacrylonitrile-based carbon fiber is 258mg; the mechanical properties of carbon fiber are as follows: breaking strength 5.3GPa, breaking strength CV value 7.9%; tensile modulus 284GPa, elongation at break 2.0%; elongation at break CV value is 7.5%.

[0257] It can be seen from the embodiments and comparative examples that the polyacrylonitrile primary fiber provided by the present invention and the polyacrylonitrile-based carbon fiber prepared using the polyacrylonitrile primary fiber have the advantages of low diameter unevenness, low hair content, high mechanical properties, and low CV values ​​of tensile strength and elongation at break, and have achieved good results.

[0258] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyacrylonitrile primary fiber, characterized in that: The value of A*B*C*100 is not greater than 30% and is not 0%; Wherein, A is the CV value of the single-filament tensile strength of 40-100 polyacrylonitrile primary fibers; B is the CV value of the single-filament tensile modulus of 40 to 100 polyacrylonitrile primary fibers; The polyacrylonitrile spun fibers are in a contracted state in the transverse direction from leaving the coagulation bath to the first winding roller in the winding roller group device. C is the width difference before and after contraction (a1-a2), measured in cm, wherein a1 is the width of the polyacrylonitrile spun fibers leaving the coagulation bath, and a2 is the width of the polyacrylonitrile spun fibers just touching the first winding roller.

2. The as-spun fiber according to claim 1, wherein The value of A*B*C*100 is not greater than 20% and is not 0%, preferably 0.5% to 20%, more preferably 0.5% to 6%, and even more preferably 0.5% to 3%; and / or A is not higher than 5%, preferably 2% to 3.5%; and / or B is not higher than 3%, preferably 1.5% to 2.5%; and / or C is 0.2 to 2.0 cm; and / or The CV value of the single-filament elongation at break of the 40-100 polyacrylonitrile primary fibers is not higher than 3%, preferably 1.5% to 2.5%.

3. The as-spun fiber according to claim 1 or 2, wherein The polyacrylonitrile nascent fibers from leaving the coagulation bath to the first crimping roller in the crimping roller assembly device are in a non-uniform thickness in the longitudinal direction, wherein the middle region is in a flat state with uniform thickness and both ends are in a round state; and / or The swelling degree of the primary fiber is 100% to 180%, preferably 120% to 180%.

4. A method for preparing the polyacrylonitrile primary fiber according to any one of claims 1 to 3, characterized in that: The wet spinning method is adopted; the preparation method comprises: the acrylonitrile copolymer spinning stock solution is extruded through a spinneret, solidified and formed, and then leaves the coagulation bath to obtain the primary fiber; During coagulation, a fiber steering device is arranged below the coagulation bath liquid surface near the coagulation bath outlet so that the angle between the plane of the coagulated fiber bundle coagulated in the coagulation bath and the vertical direction is 0° to 10°, and the fiber steering device and the center position of the spinneret are at the same level; The center point of the first crimping roller in the crimping roller group device which controls the position above the coagulation bath outlet is 10 cm to 150 cm above the coagulation bath liquid level so that the coagulated fiber bundle coagulated and formed in the coagulation bath leaves the coagulation bath.

5. The preparation method according to claim 4, wherein: The height of the center point of the first winding roller in the winding roller assembly of the coagulation bath from the liquid surface of the coagulation bath is 20 cm to 50 cm; and / or The angle between the plane of the coagulated fiber tow and the vertical direction is 0° to 5°; and / or The fiber steering device is a passive wire guide rod, the bottom surface of which is at the same level as the center of the spinneret; or the fiber steering device is a wire guide pulley, the bottom of which is at the same level as the center of the spinneret; and / or The surface roughness of the fiber steering device is Ra≤0.2; and / or; The fiber-diverting device is inert in the coagulation liquid.

6. The preparation method according to claim 4 or 5, wherein: The wrap angle between the coagulated fiber bundle and all the crimping rollers of the crimping roller assembly device is 360° to 3600°, preferably 720° to 2520°, and more preferably 1440° to 2160°; and / or The temperature of the atmosphere into which the coagulated fiber bundle enters after leaving the coagulation bath liquid surface is not higher than the coagulation bath temperature, and preferably the difference between the coagulation bath temperature and the atmosphere into which the coagulated fiber bundle enters after leaving the coagulation bath is 0°C to 15°C, preferably 2°C to 10°C, and more preferably 3°C to 8°C; and / or The coagulated fiber bundle has a width of 20 mm to 100 mm and / or an average thickness of 0.2 mm to 3.0 mm.

7. The preparation method according to any one of claims 3 to 6, wherein: The number of the coagulation baths is 1-4, and preferably the coagulation baths include: a primary coagulation bath, a secondary coagulation bath, and a tertiary coagulation bath, and the spinning stream is coagulated and formed in the primary coagulation bath, the secondary coagulation bath, and the tertiary coagulation bath in sequence, and then leaves the coagulation bath to obtain the nascent fiber; and / or The temperature of the coagulation bath is 35-80°C, preferably the temperature of the primary coagulation bath is 35-45°C; and / or the temperature of the secondary coagulation bath is 50-55°C; and / or the temperature of the tertiary coagulation bath is 70-80°C; and / or The coagulation bath liquid in the coagulation bath comprises: dimethyl sulfoxide and water, preferably the concentration of the coagulation bath liquid is not less than 10wt%, preferably the concentration of the coagulation bath liquid in the first coagulation bath is 65-78wt%; and / or the concentration of the coagulation bath liquid in the second coagulation bath is 35-50wt%; and / or the concentration of the coagulation bath liquid in the third coagulation bath is 15-20wt%; and / or The drafting ratio of the primary coagulation bath is 0.6-1.0; and / or the drafting ratio of the secondary coagulation bath is 1.0-1.1; and / or the drafting ratio of the tertiary coagulation bath is 1.05-1.

30.

8. A polyacrylonitrile-based carbon fiber, characterized in that: The value of the breaking strength CV value*breaking elongation CV value*100 of the polyacrylonitrile-based carbon fiber is not greater than 10%.

9. The polyacrylonitrile-based carbon fiber according to claim 8, wherein: The value of the breaking strength CV value*breaking elongation CV value*100 of the polyacrylonitrile-based carbon fiber is 2 to 10%, preferably 3 to 9%, and more preferably 3 to 6%; Preferably, the breaking strength CV value of the polyacrylonitrile-based carbon fiber is not greater than 6%, preferably 1 to 5%, more preferably 1 to 3%, and even more preferably 1 to 2.5%; and / or The CV value of the elongation at break of the polyacrylonitrile-based carbon fiber is not greater than 6%, preferably 1 to 5%, and more preferably 1 to 3%; and / or The diameter CV value of the polyacrylonitrile-based carbon fiber is not greater than 5%, preferably 1 to 5%, and more preferably 1 to 3%; and / or The breaking strength of the polyacrylonitrile-based carbon fiber is not less than 5.8 GPa, preferably 5.8 to 6.5 GPa; and / or The tensile modulus of the polyacrylonitrile-based carbon fiber is not less than 290 GPa, preferably 290 to 305 GPa; and / or The elongation at break of the polyacrylonitrile-based carbon fiber is 1 to 3%, preferably 1.5 to 2.5%; and / or The diameter of the polyacrylonitrile-based carbon fiber is 4.5um to 7.5um; and / or The lint content of the polyacrylonitrile-based carbon fiber with an average diameter of 5.1 um to 5.2 um and a length of 100 m is not more than 40 mg, preferably 15 mg to 40 mg.

10. A method for preparing polyacrylonitrile-based carbon fiber according to claim 9, characterized in that: The preparation method comprises: The polyacrylonitrile primary fiber according to claim 1 or 2, or the polyacrylonitrile primary fiber prepared by the method for preparing the polyacrylonitrile primary fiber according to any one of claims 3 to 8, is subjected to drawing, water washing, oiling, drying and densification, steam drawing, and heat setting to obtain polyacrylonitrile precursor, and the polyacrylonitrile precursor is subjected to pre-oxidation and carbonization to obtain polyacrylonitrile-based carbon fiber.

Citation Information

Patent Citations

  • Manufacturing method of 12K quaternary polyacrylonitrile-based carbon fiber

    CN103184588A

  • Coagulating bath tank for wet spinning and polyacrylonitrile spinning solution coagulating forming method

    CN112708945A

  • Wet spinning preparation method of high-strength high-modulus carbon fiber precursor

    CN116024676A

  • Coagulating tank for wet spinning

    CN204455372U

  • Method for producing polymer water processing film

    JP2013150961A

Cited By

  • Nitrogen-doped porous carbon electrode material and preparation method and application thereof

    CN120328535A